2021
DOI: 10.1037/pha0000510
|View full text |Cite
|
Sign up to set email alerts
|

Diversity inclusion in United States opioid pharmacological treatment trials: A systematic review.

Abstract: Pharmacological treatments for opioid use disorders (OUDs) may have mixed efficacy across diverse groups, i.e., sex/gender, race/ethnicity, and socioeconomic status (SES). The present systematic review aims to examine how diverse groups have been included in U.S. randomized clinical trials examining pharmacological treatments (i.e., methadone, buprenorphine, or naltrexone) for OUDs. PubMed was systematically searched according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 102 publications
2
13
0
Order By: Relevance
“…However, participants from diverse sex/gender and racial/ethnic backgrounds were neither routinely nor representatively included in these articles; the majority of participants included appeared to be White and males/men. These findings are largely consistent with the results of other reviews focusing on reporting and inclusion in studies focusing on addiction treatment specifically (Nalven et al, 2021;Schick et al, 2020) and in psychological research broadly (Clark et al, 2019;Gatzke-Kopp, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…However, participants from diverse sex/gender and racial/ethnic backgrounds were neither routinely nor representatively included in these articles; the majority of participants included appeared to be White and males/men. These findings are largely consistent with the results of other reviews focusing on reporting and inclusion in studies focusing on addiction treatment specifically (Nalven et al, 2021;Schick et al, 2020) and in psychological research broadly (Clark et al, 2019;Gatzke-Kopp, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…MDD among Black and Hispanic/Latinx individuals is also highly prevalent, yet Black individuals were represented at one fifth the rate of White or European Americans and Hispanic/Latinx individuals were represented at one seventh the rate of White individuals (Polo et al, 2019). In line with other pharmacological treatment research (Nalven et al, 2021), these results emphasize that individuals from diverse backgrounds are often underrepresented in clinical trials for MDD treatment, although these figures may be highly skewed or inaccurate given that only 55% of all included RCTs reported participant race/ethnicity information from 2005 to 2016 (Polo et al, 2019). This finding represents a significant increase in reporting from prior decades (Polo et al, 2019); however, this figure remains critically low given the importance of demographic factors on MDD presentation and treatment response.…”
Section: Esketaminesupporting
confidence: 80%
“…Of the 5 (23%) additional articles that reported age, 1 reported findings for pediatric populations exclusively, and the remaining 4 reported both pediatric and adult populations. 13,16,[23][24][25] Three articles (14%) focused on adults who were aged older than 40 and 60 years. 7,15,26 Nalven et al 25 found that participants in clinical trials for interventions to treat opioid use disorder did not reflect the population at risk for this particular disorder.…”
Section: Agementioning
confidence: 99%